Facile fabrication and characterization of aliphatic polyketone (PK) micro/nano fiber membranes via electrospinning and a post treatment process. Issue 2 (24th December 2020) - Hou, Jian; Park, Chanju; Jang, Wongi; Byun, Hongsik
Abstract : In this article, polyketone (PK) micro/nano fiber membranes were successfully fabricated by electrospinning and a post treatment process and the membrane characteristics were investigated. Abstract : In this article, polyketone (PK) micro/nano fiber membranes were successfully fabricated by electrospinning and a post treatment process and the membrane characteristics were investigated. The morphology of the fiber membranes showed that ambient humidity during electrospinning changed the roughness of the fiber surface and the addition of NaCl decreased the fiber diameter. In particular, the changes in surface roughness was a very rare and novel discovery. The effect of this discovery on membrane properties was also analyzed. Additionally, the nanofiber membrane was modified by in situ surface reduction. FT-IR spectroscopy indicated the successful reduction modification and water contact angle results proved the improved wetting ability by this modification process. DSC and TGA analysis showed that the micro/nano fiber membranes possessed a high melting point and thermal decomposition temperature. Mechanical tests showed that as fiber membranes, PK micro/nano fiber membranes had relatively high mechanical strength, furthermore the mechanical strength can be easily enhanced by controlling the fiber morphology. From these results, it was concluded that the PK micro/nano fiber membranes could be a promising candidate for many applications such as organic solvent-resistant membranes, high-safety battery separators, oil–water separation, etc.